Anti‐Aromaticity Relief as an Approach to Stabilize Free Radicals. Issue 47 (13th October 2021) - Zhang, Rui; Ellern, Arkady; Winter, Arthur H.
Abstract: A new strategy to stabilize free radicals electronically is described by conjugating formally antiaromatic substituents to the free radical. With an antiaromatic substituent, the radical acts as an electron sink to allow configuration mixing of a low‐energy zwitterionic state that provides antiaromaticity relief to the substituent. A combination of X‐ray crystallography, VT‐EPR and VT‐UV/Vis spectroscopy, as well as computational analysis, was used to investigate this phenomenon. We find that this strategy of antiaromaticity relief is successful at stabilizing radicals, but only if the antiaromatic substituent is constrained to be planar by synthetically imposed conformational restraints that enable state mixing. This work leads to the counterintuitive finding that increasing the antiaromaticity of the radical substituent leads to greater radical stability, providing proof of concept for a new stereoelectronic approach for stabilizing free radicals. Abstract : Radicals substituted with anti‐aromatic rings have greater stability than radicals with aromatic substituents as a result of a new stereoelectronic stabilization approach driven by anti‐aromaticity relief.